A study into the design of steerable microphone arrays - Lai, Chiong Ching; Nordholm, Sven Erik; Leung, Yee Hong (Springer, 2016)
The book covers the design formulations for broadband beamformer targeting nearfield and farfield sources. The book content includes background information on the acoustic environment, including propagation medium, the array geometries, signal models and basic beamformer designs. Subsequently it introduces design formulation for nearfield, farfield and mixed nearfield-farfield beamformers and extends the design formulation into electronically steerable beamformers. In addition, a robust formulation is introduced for all the designs mentioned.
Keywords: Microphone arrays.; elektronické knihy; electronic books